Proselytism and the Good Society: Why the Right to Share Religious Beliefs Should be Protected as a Fundamental Right - Davide ARGIOLAS (Revista Jurídica Portucalense)
This article aims to analyse the reasons why the right to proselytism, as well as the correlative freedom to change religion, should be considered fundamental rights in the light of the United Nation system of Human Rights. The main idea is that these freedoms have always been considered contentious and, thus, have not received in International Law the legal protection they deserve, despite all the benefits they bring about, both for individuals and the society in general.